Study of hydrogen injection strategy on fuel mixing characteristics of a free-piston engine - Zhaoju Qin; Fangfang Liu; Hanbo Zhang; Xingda Wang; Chenyang Yin; Weihong Weng; Zhen Han (Case Studies in Thermal Engineering, 2024)
The formation of the gas mixture in the cylinder has a significant effect on the combustion and emission of the engine. The main difference between a conventional engine and a free piston engine is that the piston movement mode is different. Therefore, a new coupled iterative method is adopted in this paper to study the injection position and duration of hydrogen fuel in a free piston engine where diesel fuels hydrogen, and reveal its influence on gas mixing and combustion in the cylinder of a free piston engine. The results show that it is suitable to spray hydrogen 55 mm from TDC. At this time, the mass fraction of H2 in the cylinder is relatively uniform, the cumulative heat release is about 620 J, and the pressure and temperature are relatively low, which are 7.2 MPa and 1529 K respectively. The duration of hydrogen injection is 0.4 ms, at this time, the mixing degree in the cylinder and the gas flow speed are better, although there is a little shortage of unburned equivalent ratio, but this has little impact on the overall, and the final cumulative heat release reaches 655 J.